2016
DOI: 10.2147/ppa.s105600
|View full text |Cite|
|
Sign up to set email alerts
|

Association between patients' beliefs and oral antidiabetic medication adherence in a Chinese type 2 diabetic population

Abstract: PurposeThe objective of this study was to identify, using the theory of planned behavior (TPB), patients’ beliefs about taking oral antidiabetic drugs (OADs) as prescribed, and to measure the correlations between beliefs and medication adherence.Patients and methodsWe performed a cross-sectional study of type 2 diabetic patients using structured questionnaires in a Chinese tertiary hospital. A total of 130 patients were enrolled to be interviewed about TPB variables (behavioral, normative, and control beliefs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…In relation to the disadvantages, the most salient belief categorized as unfavorable to the use of the tablets, was pain and gastric discomfort, nausea and diarrhea. Similar beliefs of adverse effects to the use of OAD emerged in previous research studies, with a higher frequency to the one in this study, (57.7%) 3 and (82.4%). 8 Most of the drugs in the tablet composition for T2DM have benefits because they reduce glycated hemoglobin, without risks of hypoglycemia with weight loss.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In relation to the disadvantages, the most salient belief categorized as unfavorable to the use of the tablets, was pain and gastric discomfort, nausea and diarrhea. Similar beliefs of adverse effects to the use of OAD emerged in previous research studies, with a higher frequency to the one in this study, (57.7%) 3 and (82.4%). 8 Most of the drugs in the tablet composition for T2DM have benefits because they reduce glycated hemoglobin, without risks of hypoglycemia with weight loss.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies similar beliefs were obtained. 3,8 The individuals' confidence in the established pharmacological therapy lies in obtaining controlled blood sugar levels, in the time flexibility for taking the OADs and in Beliefs about oral antidiabetic use Gouveia BLA, Sousa MM, Almeida TCF, Sousa VAG, Pereira WDF, Oliveira SHS the absence or decrease of the disease symptoms such as polyphagia, weight loss, excessive thirst, frequent urination, malaise, and headache, among others. 15 The belief identified as the advantage of "not needing to use insulin" when taking the OADs correctly points to the fear of individuals with T2DM in relation to injectable treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to identify factors that affect the medication adherence of TB patients based on Theory of Planned Behavior. The results of the study showed that the main factors of TPB (such as ATB, SN, and PBC) explain more than 96% of the other studies have also suggested that TPB became positive determinant factor related to adherence (Wu and Liu, 2016), TPB was also helpful to investigate factors underlying medication adherence (Bérubé et al, 2017), so that TPB can be used as powerful tool to predict intention and medication adherence (Zomahoun et al, 2016).…”
Section: Discussionmentioning
confidence: 96%